Electrical and Dielectric properties of 3, 3', 3'', 3'''-tetra poly (1, 4-diaminobenzen phthalate) phthalocyanine copper (II) thin films prepared by casting method. - Ziyad Falak (University of Thi-Qar Journal of Science, 2019)
In this study, 3, 3', 3'', 3'''-tetra poly (1, 4-diaminobenzen phthalate) phthalocyanine copper (II) film wasprepared by casting method. The study consists of two parts: the first includes the measurement of electricalconductivity and activation energy range (303-353) °K. The second part deals with the dielectric propertiesthat were measured at temperatures ranging from 303 to 353°K and frequency in the range (120Hz - 2MHz).Dielectric properties (dielectric permittivity, loss tangent and Ac. conductivity (σac) have also beeninvestigated. It is found that the system obeys the Maxwell-Wagner Sillars relaxation of space chargephenomenon. Permittivity, loss tangent and Ac. conductivity increase with increasing the temperature and thepermittivity decreases with the increasing of frequency. The values of ac conductivity and dc conductivitywere compared.